Combinatorics of partial wreath power of finite inverse symmetric semigroup ISd - Kochubinska, Y. (Algebra and Discrete Mathematics, 2007)
We study some combinatorial properties of ≀ k pISd. In particular, we calculate its order, the number of idempotents and the number of D-classes. For a given based graph Γ ⊂ T we compute the number of elements in its D-class DΓ and the number of R- and L-classes in DΓ.